A Basic Bivariate Structure of Personality Attributes Evident Across Nine Languages. Issue 1 (12th April 2013) - Saucier, Gerard; Thalmayer, Amber Gayle; Payne, Doris L.; Carlson, Robert; Sanogo, Lamine; Ole‐Kotikash, Leonard; Church, A. Timothy; Katigbak, Marcia S.; Somer, Oya; Szarota, Piotr; Szirmák, Zsofia; Zhou, Xinyue
Abstract Here, two studies seek to characterize a parsimonious common‐denominator personality structure with optimal cross‐cultural replicability. Personality differences are observed in all human populations and cultures, but lexicons for personality attributes contain so many distinctions that parsimony is lacking. Models stipulating the most important attributes have been formulated by experts or by empirical studies drawing on experience in a very limited range of cultures. Factor analyses of personality lexicons of nine languages of diverse provenance (Chinese, Korean, Filipino, Turkish, Greek, Polish, Hungarian, Maasai, and Senoufo) were examined, and their common structure was compared to that of several prominent models in psychology. A parsimonious bivariate model showed evidence of substantial convergence and ubiquity across cultures. Analyses involving key markers of these dimensions in English indicate that they are broad dimensions involving the overlapping content of the interpersonal circumplex, models of communion and agency, and morality/warmth and competence. These "Big Two" dimensions—Social Self‐Regulation and Dynamism—provide a common‐denominator model involving the two most crucial axes of personality variation, ubiquitous across cultures. The Big Two might serve as an umbrella model serving to link diverse theoretical models and associated research literatures.